Influence of preparation method on activity and stability of Ni catalysts supported on Gd doped ceria in dry reforming of methane - Gurav, Hanmant R.; Dama, Srikanth; Samuel, Violet; Chilukuri, Satyanarayana (Journal of CO2 Utilization, 2017)
Nickel catalysts supported on Gd doped ceria (NGDC), with various Ni content, were prepared through different preparation routes and evaluated for dry reforming of methane (DRM). Their detailed characterization revealed that method of preparation plays an important role in Ni dispersion, with catalysts prepared through co-precipitation showing high Ni dispersion. The co-precipitated 12NGDC-cp catalyst with 12 wt% NiO was found to be superior in terms of high CO2 and CH4 conversions compared to catalysts prepared through citrate gel or impregnation methods Even H-2 and CO yields are high on this catalyst, while it shows excellent durability with stable activity even after 100 h on-stream. Thermogravimetric analysis of spent catalyst showed presence of coke, with transmission electron microscopic studies pointing to the presence of Ni crystallites at the mouth of the carbon whiskers. These Ni crystallites appear to be still active for DRM reaction. Among the spent catalysts, the carbon formation was high on catalysts that have bigger Ni crystallites, with the catalysts prepared through impregnation and citrate gel methods having higher coke. Investigations also reveal that the conversion of active (amorphous) carbon into stable (graphitic) carbon depends on the Ni crystallite size, temperature and duration of the reaction. These studies demonstrate that Gd doped ceria is a good support for Ni, to obtain high DRM activity and very good on-stream stability provided the catalysts are prepared through an appropriate method.

Active and durable alkaline earth metal substituted perovskite catalysts for dry reforming of methane - Dama, Srikanth; Ghodke, Seema R.; Bobade, Richa; Gurav, Hanmant R.; Chilukuri, Satyanarayana (Applied Catalysis B - Environmental, 2018)
Dry reforming of methane is an important process for the utilization of CO2 and to get valuable synthesis gas. Alkaline earth metal substituted MZr1-xNixO3-delta perovskites were synthesized by citrate gel method, characterized and evaluated for dry reforming methane. Characterization results show that the type of alkaline earth substituted at the A site of the perovskite oxide plays an important role in terms of structure, basicity, oxygen deficiency and Ni dispersion. Calcium substituted CaZr0.8Ni0.2O3-delta catalyst shows superior activity in terms of high CH4 and CO2 conversion, while maintaining the activity even after 500 h of reaction. Mechanistic investigations were carried out using transient pulse experiments and insitu FTIR-diffuse reflectance spectroscopy. These experiments reveal that redox property and basicity play important role in activation and sustaining the reforming reaction. Insitu FTIR measurements show that surface hydroxyl groups of the support are vital for high activity and durability of CaZr0.8Ni0.2O3-delta catalyst. XRD and TGA analysis of catalysts after reaction show the structures are retained, but peaks pertaining to coke were observed on SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts. On the otherhand, CaZr0.8Ni0.2O3-delta catalyst had only amorphous carbon even after 500 h of reaction. HRTEM studies revealed that SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts deactivated mostly due to the formation of carbon nanotubes with Ni embedded in them. Raman and XPS analysis helped in identifying types of coke precursors present on the catalysts. The investigation also illustrate that type of carbon formed depends on the basicity of perovskite oxide, metal to support interaction, Ni crystallite size, surface hydroxyl groups and oxygen defects. This study clearly demonstrated that CaZr0.8Ni0.2O3-delta is an excellent catalyst for dry reforming reaction with long life.

Tuning the dimensionality of layered Srn+1Tin−xNixO3n+1 perovskite structures for improved activity in syngas generation - Dama, Srikanth (Journal of Catalysis, 2018)
Interest in perovskite type oxides is growing due to their versatile catalytic applications. A series of Ruddlesden-Popper (RP) type layered perovskite oxides Srn+1Tin−xNixO3n+1 were prepared and evaluated for their catalytic activity in steam reforming, CO2 reforming and bi-reforming of methane. These materials, prepared through citrate gel method were characterized to understand their structure and Ni reducibility. Substitution of Ni in RP phases was established through refinement of XRD powder pattern. During methane reforming, the catalytic activity increased with the order of RP phase of SrTi1−xNixO3−δ (n = ∞). TPR results show variation in Ni reducibility with the order of RP phase, while TPD-O2 study helped to estimate oxygen vacancies. These vacancies seem to influence catalytic activity during methane reforming. Transient pulse experiments show that CO2 dissociates over oxygen vacancies to give CO and oxygen, with later replenishing lattice oxygen in SrTi0.8Ni0.2O3−δ (n = ∞) phases. Highly labile oxygen vacancies generated in the bulk of SrTi0.8Ni0.2O3−δ must be migrating to the surface, helping in the removal of coke formed. Characterization of catalysts after reaction helped in better understanding of coke precursors.
Keywords: Dry reforming; NickelSyngas; Ruddlesden-Popper (RP) perovskites; Steam reforming

Molybdenum carbide catalyst for the reduction of CO2 to CO: surface science aspects by NAPPES and catalysis studies - Reddy, Kasala Prabhakar; Dama, Srikanth; Mhamane, Nitin B.; Ghosalya, Manoj K.; Raja, Thirumalaiswamy; Satyanarayana, Chilukuri V.; Gopinath, Chinnakonda S. (Dalton Transactions, 2019)
Carbon dioxide is a greenhouse gas, and needs to be converted into one of the useful feedstocks, such as carbon monoxide and methanol. We demonstrate the reduction of CO2 with H-2 as a reducing agent, via a reverse water gas shift (RWGS) reaction, by using a potential and low cost Mo2C catalyst. Mo2C was evaluated for CO2 hydrogenation at ambient pressure as a function of temperature, and CO2 : H-2 ratio at a gas hourly space velocity (GHSV) of 20 000 h(-1). It is demonstrated that the Mo2C catalyst with 1 : 3 ratio of CO2 : H-2 is highly active (58% CO2 conversion) and selective (62%) towards CO at 723 K at ambient pressure. Both properties (basicity and redox properties) and high catalytic activity observed with Mo2C around 700 K correlate well and indicate a strong synergy among them towards CO2 activation. X-ray diffraction and Raman analysis show that the Mo2C catalyst remains in the beta-Mo2C form before and after the reaction. The mechanistic aspects of the RWGS reaction were determined by near-ambient pressure X-ray photoelectron spectroscopy (NAPXPS) with in situ generated Mo2C from carburization of Mo-metal foil. NAPXPS measurements were carried out at near ambient pressure (0.1 mbar) and various temperatures. Throughout the reaction, no significant changes in the Mo2+ oxidation state (of Mo2C) were observed indicating that the catalyst is highly stable; C and O 1s spectral results indicate the oxycarbide species as an active intermediate for RWGS. A good correlation is observed between catalytic activity from atmospheric pressure reactors and the electronic structure details derived from NAPXPS results, which establishes the structure-activity correlation.